Educational Management in Nigeria: Challenges and Way Forward (Kwasu International Journal of Educational Management and Leadership, 2026)
Education is a lifelong process that helps individuals to acquire the basic knowledge, skills, and values needed to become functional members of the society. Thus, it becomes imperative that a nations education is not toiled with but instead be properly managed by professional managers who are vested with the appropriate knowledge to adequately execute planned educational policies and programmes. However, In Nigeria, educational management faces numerous challenges that affect the overall quality of education. Thus, this paper examines educational management in Nigeria: challenges and way forward. The concepts of education, management and educational management were looked into. Also, the roles of educational management were examined. The challenges of the efficacy of educational management were equally elucidated among which are: poor funding, inequality in resource distribution, political consideration in management selection and inadequate professional development programme among others. The paper concludes that educational management is a necessity for the advancement of educational programmes in Nigeria. The paper suggests among other that stakeholders in education should support timely and affordable professional training and retraining programmes for education managers at all levels of education, educational managers should be recruited into educational institutions and agencies and appointed to handle educational programmes by merit rather than connection. Also, there is needs to re-evaluate, re-position the management of educational system n both government and non-government institutions across Nigeria to address to enhance the efficacy of the system.